Preparation method of special flame retardant for rigid polyurethane foam
By utilizing the reaction of hollow silica microspheres with silane coupling agents and basic aminosulfonates during the preparation of polyurethane rigid foam, a density-matched flame retardant specifically for polyurethane rigid foam is prepared, which solves the problems of uneven dispersion and poor stability and improves the flame retardant properties.
Patent Information
- Application Number
- CN202510522987.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-24
- Publication Date
- 2025-09-09
AI Technical Summary
Sulfonate flame retardants are unevenly dispersed, have poor stability and poor compatibility in polyurethane rigid foam materials, which affects their flame retardant properties, and existing technologies have failed to effectively solve these problems.
In an ethanol aqueous solution, a flame retardant specifically for polyurethane rigid foam is prepared by reacting hollow silica microspheres with a silane coupling agent with epoxy functional groups in an alkaline environment, and then reacting with basic aminosulfonate. Its density matches that of the polyurethane rigid foam precursor composition, and the flame retardant is fixed inside the polymer through chemical bonds.
The uniform dispersion and stability of the sulfonate flame retardant in the polyurethane rigid foam are achieved, the flame retardant performance is improved, and the flame retardant effect of the polyurethane rigid foam is ensured.
Smart Images

Figure CN120607825A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of flame retardant materials, and in particular to a method for preparing a special flame retardant for polyurethane rigid foam. Background Art
[0002] Polyurethane rigid foam boasts excellent thermal insulation, high mechanical properties, waterproof and moisture-proof properties, dimensional stability, sound insulation, and chemical resistance, making it widely used in insulation, packaging, and construction materials. However, due to its porosity and low density, polyurethane rigid foam exhibits a certain degree of flammability. This flammability stems primarily from elements such as carbon and hydrogen contained in its chemical structure. During combustion, flammable gases are released, making firefighting difficult and posing a threat to human health and the environment.
[0003] Currently, the addition of flame retardants can reduce the flammability of polyurethane rigid foam and improve its fire resistance. Sulfonate flame retardants are a class of highly effective halogen-free flame retardants. The mechanism by which sulfonates exert their flame-retardant effect in polyurethane rigid foam differs significantly from that of other flame retardants. The main mechanism of sulfonate flame retardancy in polyurethane rigid foam is as follows: It is generally believed that the sulfonic acid groups in sulfonates decompose before the polyurethane rigid foam upon heating. During the condensed phase catalytic synthesis of rigid foam, during the chain branching reaction during the degradation of the resin, the sulfonic acid groups in the sulfonate react with heat to produce acidic substances such as SO2 and SO3. These accelerate the charring process in the condensed phase, forming a denser char layer that blocks the transfer of heat and combustible gases. Furthermore, the alkali metal ions in the sulfonate also accelerate the degradation of the resin into char, forming a dense char layer. Due to the low thermal decomposition temperature of sulfonate flame retardants and their low usage, they decompose and become ineffective at temperatures above 200°C. Considering that polyurethane rigid foam is generally used as a thermal insulation material and its operating temperature hardly exceeds 70°C, there is no problem in using sulfonate flame retardants to improve the flame retardancy of polyurethane rigid foam materials.
[0004] As we all know, sulfonate flame retardants are widely used in polycarbonate and other polymer materials as a highly efficient and environmentally friendly halogen-free flame retardant. However, they are not widely used in polyurethane rigid foams. The reasons are mainly as follows:
[0005] On the one hand, sulfonate flame retardants are often solid powders, which cannot be stably and evenly dispersed in the liquid polyether precursor combination of polyurethane rigid foam for a long time; on the other hand, among sulfonate flame retardants, alkali metal salts and ammonium salts have the best flame retardant effect, but they are easy to absorb water and hydrolyze, and although alkaline earth metal salts and other high-valent metal salts are insoluble in water, they have poor flame retardant effect and are expensive, and sulfonic acid is a liquid, and its strong acidity will destroy the catalyst in the polyurethane rigid foam; third, sulfonate flame retardants have poor compatibility with polyurethane rigid foam. Polyurethane rigid foam is an organic matter, while sulfonate flame retardants are inorganic and are small-molecule alkali metal salts. The two cannot be miscible, resulting in sulfonate flame retardants deteriorating the mechanical structure and pore structure of polyurethane rigid foam. Moreover, if the amount of sulfonate flame retardant is too small, the uneven mixing and enrichment will seriously affect the flame retardant properties of polyurethane rigid foam. Summary of the Invention
[0006] The purpose of the present invention is to address the deficiencies of the above-mentioned technologies and provide a method for preparing a special flame retardant for polyurethane rigid foam. During the preparation process of polyurethane rigid foam, the sulfonate flame retardant is evenly dispersed, and the stability and compatibility are improved, so as to achieve wide application in polyurethane rigid foam.
[0007] To this end, the present invention provides a method for preparing a flame retardant specifically for polyurethane rigid foam, comprising the following steps:
[0008] In an ethanol aqueous solution, under an alkaline environment, hollow silica microspheres react with a silane coupling agent with an epoxy functional group to obtain surface-activated hollow silica microspheres; the surface-activated hollow silica microspheres react with basic aminosulfonate or aminosulfonate guanidine. After the reaction is completed, post-treatment is performed to obtain a flame retardant specifically for polyurethane rigid foam.
[0009] Preferably, the ethanol aqueous solution is prepared by mixing ethanol and deionized water in a mass ratio of 980:18.
[0010] Preferably, the alkaline environment is sodium hydroxide or potassium hydroxide.
[0011] Preferably, the alkaline environment is sodium hydroxide, and the mass ratio of the ethanol aqueous solution to the sodium hydroxide is 998:0.2-2.
[0012] Preferably, the mass ratio of the hollow silica microspheres, the silane coupling agent, and the basic aminosulfonate or guanidine aminosulfonate is 300-500:16.5-27.5:75-125.
[0013] Preferably, the density of the hollow silica microspheres is 1.03 to 1.09 g / cm 3 The particle size of the hollow silica microspheres is 7 to 48 μm.
[0014] Preferably, the basic sulfamate is selected from sodium sulfamate or potassium sulfamate.
[0015] Preferably, the silane coupling agent with epoxy functional group is KH560.
[0016] Preferably, the reaction temperature of the hollow silica microspheres and the silane coupling agent is 40-90°C.
[0017] Preferably, the post-treatment method includes: vacuum filtration and drying the obtained filter cake.
[0018] Preferably, the drying temperature is 100°C.
[0019] The beneficial effects of the present invention are as follows: the present invention provides a method for preparing a flame retardant specifically for polyurethane rigid foam. By adjusting the raw material ratio, reaction conditions, the density of silica microspheres, etc., the density of the target product of the present invention, the flame retardant specifically for polyurethane rigid foam (solid), is made the same as or not much different from the density of the precursor composite polyether (liquid) in the actual production process of polyurethane rigid foam. The present invention, as a solid flame retardant, can be suspended and dispersed in the composite polyether in a liquid state, so that the two are evenly distributed. In addition, because the chemical bonds of the aminosulfonate are bound to the surface of the silica microspheres, it will not be lost even if it absorbs water; at the same time, the amino group can react with the epoxy functional group to form a hydroxyl group and an imino group, which can react with the precursor isocyanate in the polyurethane rigid foam, thereby being firmly fixed inside the polymer to form a reactive flame retardant, thereby ensuring the flame retardant properties of the polyurethane rigid foam. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments or descriptions of the prior art. Obviously, the drawings described below are only some embodiments of the present application.
[0021] Figure 1 Schematic diagram of the synthesis process of the flame retardant for polyurethane rigid foam of the present invention;
[0022] Figure 2 These are the results of Fourier infrared spectroscopy analysis of hollow silica microspheres and the flame retardant for polyurethane rigid foam prepared in Example 1. DETAILED DESCRIPTION
[0023] In order to make the technical problems, technical solutions and beneficial effects to be solved by this application more clearly understood, the present application is further described in detail below with reference to the accompanying drawings and examples. It should be understood that the specific embodiments described herein are merely for the purpose of explaining this application and are not intended to limit this application. The methods used in this invention are conventional methods unless otherwise specified; the raw materials and devices used are conventional commercially available products unless otherwise specified.
[0024] Figure 1 The invention discloses a synthetic process for a flame retardant specifically for polyurethane rigid foam. The invention provides the following steps: a silane coupling agent with epoxy functional groups is added to closed-cell hollow silica microspheres in an ethanol aqueous solution under an alkaline environment. For example, KH-560 is used as an example. The ethoxy groups of KH-560 are hydrolyzed under the action of water to generate silanol groups. Subsequently, the silanol groups react with hydroxyl groups on the surface of the silica microspheres to form strong silicon-oxygen bonds, thereby grafting a large number of epoxy functional groups onto the surface of the silica microspheres. A flame-retardant basic aminosulfonate (such as sodium aminosulfonate) or aminoguanidine sulfonate is then added. The amino groups of the aminosulfonate can undergo a ring-opening reaction with the epoxy functional groups on the surface of the silica microspheres, thereby grafting the epoxy functional groups onto the surface of the silica microspheres. Finally, the flame retardant specifically for polyurethane rigid foam is prepared.
[0025] Example 1
[0026] This embodiment 1 provides a method for preparing a flame retardant specifically for polyurethane rigid foam, comprising the following steps:
[0027] Take 980g of deionized water, add 18g of ethanol and 2g of sodium hydroxide, the mass ratio of ethanol water solution to sodium hydroxide is 998:2, stir for 1-2 minutes at a speed of 300-350 rpm, then add 400g of hollow silica microspheres (the density of a single hollow silica microsphere is 1.06g / cm 3 , average particle size 24 μm), heating, and controlling the temperature at 70°C; while stirring, quickly add 22 g of silane coupling agent KH560, stir and react for 1 hour, then add 100 g of sodium aminosulfonate at a rate of 2 g / min, still controlling the temperature at 70°C, stir and react for 2 hours, then cool to room temperature, vacuum filter, and dry the obtained filter cake at 100°C for 12 hours to obtain a flame retardant powder for polyurethane rigid foam.
[0028] The target product obtained in Example 1, the flame retardant powder for polyurethane rigid foam, weighed 503 g, with a yield of 96.4% and a density of 1.12 g / cm 3 .
[0029] Calculation formula: Yield = actual weight of target product / theoretical weight of target product
[0030] The theoretical weight of the target product = the weight of the hollow silica microspheres + the weight of the silane coupling agent + the weight of the aminosulfonate
[0031] Example 2
[0032] This Example 2 provides a method for preparing a flame retardant specifically for polyurethane rigid foam. The method is different from the preparation steps of Example 1 except that the amount of hollow silica microspheres added is 300 g, the amount of silane coupling agent KH560 added is 16.5 g, and the amount of sodium aminosulfonate added is 75 g. The other contents are the same and will not be repeated.
[0033] After measurement and calculation, the polyurethane rigid foam special flame retardant powder obtained in Example 2 weighed 370.7g, with a yield of 94.7% and a density of 1.11g / cm 3 .
[0034] It can be seen that compared with Example 1, after reducing the amount of hollow silica microspheres, silane coupling agent KH560, and sodium sulfamate in Example 2, the yield of the target product decreased from 96.4% to 94.7%, and the density decreased from 1.12 g / cm 3 Down to 1.11g / cm 3 .
[0035] Example 3
[0036] This Example 3 provides a preparation method for a flame retardant specifically for polyurethane rigid foam. The method is different from the preparation steps of Example 1 except that the amount of hollow silica microspheres added is 500 g, the amount of silane coupling agent KH560 added is 27.5 g, and the amount of sodium aminosulfonate added is 125 g. The other contents are the same and will not be repeated.
[0037] After measurement and calculation, the polyurethane rigid foam flame retardant powder obtained in Example 3 weighed 580.7 g, with a yield of 89.0% and a density of 1.14 g / cm 3 .
[0038] It can be seen that compared with Example 1, after increasing the amount of hollow silica microspheres, silane coupling agent KH560, and sodium sulfamate in Example 3, the yield of the target product decreased from 96.4% to 89.0%, and the density decreased from 1.12 g / cm 3 Increased to 1.14g / cm 3 .
[0039] Example 4
[0040] This embodiment 4 provides a preparation method of a special flame retardant for polyurethane rigid foam. The content of the preparation method is different from the content of the preparation steps in embodiment 1, except that the sodium aminosulfonate in embodiment 1 is replaced by potassium aminosulfonate. The other contents are the same and will not be repeated.
[0041] After measurement and calculation, the polyurethane rigid foam special flame retardant powder obtained in Example 4 weighed 510.7g, with a yield of 97.8% and a density of 1.13g / cm 3.
[0042] It can be seen that compared with Example 1, after sodium sulfamate was replaced by potassium sulfamate in Example 4, the yield of the target product increased from 96.4% to 97.8%, and the yield increased by 1.4%. 3 Increased to 1.13g / cm 3 , since the current price of potassium sulfamate is much more expensive than potassium sulfamate, and potassium ions may affect the catalyst system of polyurethane. The main reason is that potassium ions are one of the strong catalysts for polyurethane curing reaction. Therefore, sodium sulfamate is preferably used.
[0043] Example 5
[0044] This Example 5 provides a preparation method of a special flame retardant for polyurethane rigid foam. The content of the preparation method is different from the content of the preparation steps in Example 1, except that the sodium aminosulfonate in Example 1 is replaced with guanidine aminosulfonate. The other contents are the same and will not be repeated.
[0045] After measurement and calculation, the polyurethane rigid foam special flame retardant powder obtained in Example 5 weighed 508.3g, with a yield of 97.4% and a density of 1.11g / cm 3 .
[0046] It can be seen that compared with Example 1, after sodium sulfamate was replaced with guanidine sulfamate in Example 5, the yield of the target product increased from 96.4% to 97.4%, and the yield increased by 1.0%. 3 Down to 1.11g / cm 3 , so guanidine sulfamate is also a good choice.
[0047] Example 6
[0048] This Example 6 provides a preparation method of a special flame retardant for polyurethane rigid foam. The content of the method is different from the preparation steps of Example 1, except that the sodium aminosulfonate in Example 1 is replaced by ammonium aminosulfonate. The other contents are the same and will not be repeated.
[0049] After measurement and calculation, the polyurethane rigid foam flame retardant powder obtained in Example 6 weighed 496.4 g, with a yield of 95.1% and a density of 1.12 g / cm 3 .
[0050] It can be seen that compared with Example 1, after sodium sulfamate was replaced with ammonium sulfamate in Example 6, the yield of the target product obtained decreased from 96.4% to 95.1%, a decrease of 1.3%; the density did not change, so ammonium sulfamate is also a good choice.
[0051] Example 7
[0052] This Example 7 provides a preparation method of a special flame retardant for polyurethane rigid foam. The content is different from the preparation steps of Example 1, except that the amount of silane coupling agent KH560 added is 25g. Other contents are the same and will not be repeated.
[0053] The polyurethane rigid foam flame retardant powder obtained in Example 7 weighed 517 g, with a yield of 98.5% and a density of 1.17 g / cm 3 .
[0054] It can be seen that compared with Example 1, after increasing the amount of silane coupling agent KH560 from 22g to 25g in Example 7, the yield of the target product increased from 96.4% to 98.5%, a 2.1% increase in yield; the density increased from 1.12g / cm 3 Increased to 1.17g / cm 3 Preliminary analysis showed that as the amount of silane coupling agent KH-560 increased, the number of epoxy functional groups on the surface of the hollow silica microspheres that could react with sodium sulfamate increased, so the loss of unreacted sodium sulfamate decreased, the cross-linking density increased, and the yield of the target product increased slightly, while the density increased significantly.
[0055] Example 8
[0056] This Example 8 provides a preparation method of a special flame retardant for polyurethane rigid foam. The content is different from the preparation steps of Example 1, except that the amount of silane coupling agent KH560 added is 17g. Other contents are the same and will not be repeated.
[0057] After measurement and calculation, the polyurethane rigid foam special flame retardant powder obtained in Example 8 weighed 491.4g, with a yield of 95% and a density of 1.09g / cm 3 .
[0058] It can be seen that compared with Example 1, after the addition amount of silane coupling agent KH560 in Example 8 was reduced from 22g to 17g, the yield of the target product obtained was reduced from 96.4% to 95%, and the yield decreased by 1.4%; the density was reduced from 1.12g / cm 3 Reduced to 1.09g / cm 3 Preliminary analysis showed that as the amount of silane coupling agent KH-560 was reduced, the number of epoxy functional groups on the surface of the hollow silica microspheres that could react with sodium sulfamate decreased. As a result, the amount of sodium sulfamate that was not involved in the reaction increased, the cross-linking density decreased, and the yield of the target product decreased slightly. At the same time, the density decreased significantly.
[0059] Example 9
[0060] This Example 9 provides a preparation method for a special flame retardant for polyurethane rigid foam. Compared with the preparation steps of Example 1, the difference is that the average particle size of the hollow silica microspheres is 7 μm. Other contents are the same and will not be repeated.
[0061] The polyurethane rigid foam flame retardant powder obtained in Example 9 weighed 486.3 g, with a yield of 93.1% and a density of 1.09 g / cm 3 .
[0062] It can be seen that compared with Example 1, after the average particle size of the hollow silica microspheres in Example 9 was changed from 24 μm to 7 μm, the yield of the target product was reduced from 96.4% to 93.1%, a decrease of 3.3%; the density was reduced from 1.12 g / cm 3 Reduced to 1.09g / cm 3 Preliminary analysis indicates that the decrease in target product yield is due to the smaller hollow microspheres, which are more likely to pass through the filter cloth and be lost during the filtration process. Furthermore, since smaller hollow silica microspheres produce denser filter cakes, this significantly slows the filtration process. Therefore, in actual production, the appropriate hollow microsphere size should be selected based on actual conditions.
[0063] Example 10
[0064] This Example 10 provides a preparation method for a special flame retardant for polyurethane rigid foam. Compared with the preparation steps of Example 1, the difference is that the average particle size of the hollow silica microspheres is 48 μm. Other contents are the same and will not be repeated.
[0065] After measurement and calculation, the polyurethane rigid foam special flame retardant powder obtained in Example 10 weighed 491.4g, with a yield of 95% and a density of 1.09g / cm 3 .
[0066] It can be seen that compared with Example 1, after the average particle size of the hollow silica microspheres in Example 10 was changed from 24 μm to 48 μm, the yield of the target product was reduced from 96.4% to 95%, a decrease of 1.4%; the density was reduced from 1.12 g / cm 3 Reduced to 1.09g / cm 3. Preliminary analysis shows that the slight decrease in yield is mainly due to two reasons. On the one hand, at the same weight, the particle size of the hollow silica microspheres has doubled. According to the sphere formula, the specific surface area of hollow microspheres with large particle size is reduced, while the amount of flame retardant that can be loaded remains unchanged, which leads to the surface of the microspheres being covered with flame retardants, resulting in a decrease in the flame retardant loaded on their surface, so the yield has decreased; on the other hand, it is not easy to pass through the filter cloth and be lost during the filtration process. Considering the use of the prepared flame retardant in the subsequent process of polyurethane rigid foam spraying, if the particle size of the hollow silica microspheres is too large, there will be a risk of clogging the nozzle. For example, if the nozzle diameter is 100μm, if the average particle size of the hollow silica microspheres is too large, exceeding 50μm, two or more hollow silica microspheres exceeding 50μm will agglomerate and pass through the nozzle at the same time, which will clog the nozzle. Therefore, it is necessary to select hollow microspheres with appropriate particle size according to the actual situation, or select a nozzle with a matching diameter according to the particle size of the hollow microspheres.
[0067] Example 11
[0068] This Example 11 provides a preparation method for a special flame retardant for polyurethane rigid foam. The content of the preparation step is different from the content of the preparation step in Example 1, except that the amount of sodium hydroxide used in the reaction process is 8 g, and the mass ratio of ethanol aqueous solution to sodium hydroxide is 998:8. The other contents are the same and will not be repeated.
[0069] After measurement and calculation, the polyurethane rigid foam special flame retardant powder obtained in Example 11 weighed 472.1g, with a yield of 90.4% and a density of 1.08g / cm 3 .
[0070] It can be seen that compared with Example 1, after significantly increasing the amount of sodium hydroxide in Example 11, the yield of the target product obtained was reduced from 96.4% to 90.4%, a decrease of 6.0%; the density was reduced from 1.12 g / cm 3 Reduced to 1.08g / cm 3 Preliminary analysis indicates that significantly increasing the amount of sodium hydroxide increases the pH of the reaction system, significantly increasing the hydrolysis rate of KH560. As a result, some KH560 undergoes a polycondensation reaction with its own silanol groups before it can fully react with the hydroxyl groups on the surface of the hollow silica microspheres. This results in a decrease in the amount of KH560 hydrolyzate that reacts with the hydroxyl groups on the hollow silica microspheres. This, in turn, reduces the number of epoxy functional groups on the hollow silica microspheres that react with sodium sulfamate, significantly decreasing the yield of the target product. The slight decrease in density is due to a decrease in the amount of KH560 and sulfamate participating in the reaction on the surface of the hollow silica microspheres.
[0071] Example 12
[0072] This Example 12 provides a preparation method for a special flame retardant for polyurethane rigid foam. The content of the preparation method is different from the content of the preparation steps in Example 1, except that the amount of sodium hydroxide used in the reaction process is reduced to 0.2 g, and the mass ratio of ethanol aqueous solution to sodium hydroxide is 998:0.2. The other contents are the same and will not be repeated.
[0073] The polyurethane rigid foam flame retardant powder obtained in Example 12 weighed 476.3 g, with a yield of 91.2% and a density of 1.09 g / cm 3 .
[0074] It can be seen that compared with Example 1, after Example 12 greatly reduces the amount of sodium hydroxide, the yield of the target product obtained is reduced from 96.4% to 91.2%, a decrease of 5.2%; the density is reduced from 1.12 g / cm 3 Reduced to 1.09g / cm 3 . Preliminary analysis shows that a significant reduction in the amount of sodium hydroxide will reduce the pH value in the reaction system, resulting in a significant decrease in the hydrolysis rate of KH560. A large amount of KH560 that does not participate in the reaction exists in the reaction system, and the KH560 that does not participate in the reaction is lost by filtration during the subsequent filtration process. Of course, the yield can be increased by significantly extending the reaction time, but the production capacity will be greatly reduced. Therefore, in actual production, it is very necessary to set an appropriate pH value to balance the yield and production capacity of the target product.
[0075] Example 13
[0076] This Example 13 provides a preparation method of a special flame retardant for polyurethane rigid foam. The content is different from the preparation steps of Example 1 in that the temperature during the reaction is controlled at 40°C. Other contents are the same and will not be repeated.
[0077] After measurement and calculation, the polyurethane rigid foam flame retardant powder obtained in Example 13 weighed 483.9 g, with a yield of 92.7% and a density of 1.10 g / cm 3 .
[0078] It can be seen that compared with Example 1, Example 13 reduces the reaction temperature from 70°C to 40°C, and the yield of the target product obtained is reduced from 96.4% to 92.7%, a decrease of 3.7%; the density is reduced from 1.12 g / cm 3 Reduced to 1.10g / cm 3Preliminary analysis indicates that lowering the reaction temperature slows the hydrolysis of the silane coupling agent KH560, resulting in a large amount of unreacted KH560 in the reaction system. This unreacted KH560 is lost during the subsequent filtration process, resulting in a decrease in the yield of the target product. The slight decrease in density is attributed to a decrease in the amount of KH560 and aminosulfonate participating in the reaction on the surface of the hollow silica microspheres.
[0079] Example 14
[0080] This Example 14 provides a preparation method for a special flame retardant for polyurethane rigid foam. The method is different from the preparation steps of Example 1 in that the temperature during the reaction is controlled at 90°C. Other contents are the same and will not be repeated.
[0081] After measurement and calculation, the polyurethane rigid foam special flame retardant powder obtained in Example 14 weighed 465.1g, with a yield of 90.0% and a density of 1.08g / cm 3 .
[0082] It can be seen that compared with Example 1, in Example 14, the temperature of the reaction process was increased from 70°C to 90°C, and the yield of the target product was reduced from 96.4% to 90.0%, a decrease of 6.4%; the density was reduced from 1.12 g / cm 3 Reduced to 1.08g / cm 3 Preliminary analysis indicates that increasing the reaction temperature accelerates the hydrolysis of the silane coupling agent KH560, causing some of it to undergo a polycondensation reaction with the hydroxyl groups on the surface of the hollow silica microspheres before it can fully react with them. This results in a reduction in the amount of KH560 hydrolyzate available to react with the hydroxyl groups on the hollow silica microspheres. This, in turn, reduces the number of epoxy functional groups on the hollow silica microspheres available to react with sodium sulfamate, leading to a decrease in the yield of the target product. The slight decrease in density is attributed to a decrease in the amount of KH560 and sulfamate reacting on the surface of the hollow silica microspheres.
[0083] Example 15
[0084] This Example 15 provides a method for preparing a flame retardant specifically for polyurethane rigid foam. The method is different from the preparation steps of Example 1 in that the density of the hollow silica microspheres selected during the reaction is 1.09 g / cm 3 , the other contents are the same and will not be repeated.
[0085] After measurement and calculation, the polyurethane rigid foam special flame retardant powder obtained in Example 15 weighed 502.7g, with a yield of 96.3% and a density of 1.15g / cm 3 .
[0086] It can be seen that compared with Example 1, Example 15 increases the density of hollow silica microspheres from 1.06 g / cm 3 Adjusted to 1.09g / cm 3 The yield of the target product was reduced from 96.4% to 96.3%, with almost no change; the density was reduced from 1.12 g / cm 3 Increased to 1.15g / cm 3 Preliminary analysis shows that increasing the density of hollow silica microspheres does not significantly change the yield of the corresponding flame retardant powder for polyurethane rigid foam, while the density is improved. This indicates that adjusting the density of hollow silica microspheres does not affect the yield of the chemical reaction when other conditions remain unchanged.
[0087] Example 16
[0088] This Example 16 provides a method for preparing a flame retardant specifically for polyurethane rigid foam. The method is different from the preparation steps of Example 1 in that the density of the hollow silica microspheres selected during the reaction is 1.03 g / cm 3 , the other contents are the same and will not be repeated.
[0089] After measurement and calculation, the polyurethane rigid foam flame retardant powder obtained in Example 16 weighed 504.1 g, with a yield of 96.6% and a density of 1.09 g / cm 3 .
[0090] It can be seen that compared with Example 1, Example 16 increases the density of hollow silica microspheres from 1.06 g / cm 3 Adjusted to 1.03g / cm 3 The yield of the target product increased from 96.4% to 96.6%, with almost no change; the density increased from 1.12 g / cm 3 Reduced to 1.09g / cm 3 Preliminary analysis shows that reducing the density of hollow silica microspheres does not significantly change the yield of the corresponding flame retardant powder for polyurethane rigid foam, while the density decreases. This indicates that adjusting the density of hollow silica microspheres does not affect the yield of the chemical reaction when other conditions remain unchanged.
[0091] Comparative Example 1
[0092] Comparative Example 1 provides a preparation method of a special flame retardant for polyurethane rigid foam. Compared with the preparation steps of Example 1, the difference is that the amount of hollow silica microspheres added is 620 g, the amount of silane coupling agent KH560 added is 34.1 g, and the amount of sodium aminosulfonate added is 155 g. The other contents are the same and will not be repeated.
[0093] It was observed on site that with the continuous addition of sodium sulfamate and the progress of the reaction, the viscosity of the system became increasingly higher and the stirring motor became noticeably hotter. When the amount of sodium sulfamate added reached 110g, the motor overheated and stopped. Moreover, the reactor was very viscous and had extremely poor fluidity, so it was forced to stop. As a result, sodium sulfamate could not be added according to the originally planned amount, and industrial production was no longer possible at this point.
[0094] Comparative Example 2
[0095] Comparative Example 2 provides a preparation method of a special flame retardant for polyurethane rigid foam. Compared with the preparation steps of Example 1, the difference is that the sodium aminosulfonate in Example 1 is replaced by iron aminosulfonate. The other contents are the same and will not be repeated.
[0096] On-site observations showed that as the reaction progressed, the solution turned brown and its pH decreased toward acidity. Preliminary analysis revealed that the hydrolysis of ferric sulfamate to form a brown precipitate of ferric hydroxide caused system instability and the presence of large amounts of hydroxide impurities, making the resulting flame retardant unusable.
[0097] Comparative Example 3
[0098] Comparative Example 3 provides a preparation method for a special flame retardant for polyurethane rigid foam. Its content is compared with the preparation steps of Example 1, except that: the amount of sodium hydroxide added is 9 g, and the mass ratio of ethanol aqueous solution to sodium hydroxide is 998:9; after the reaction is completed, it is cooled to room temperature and vacuum filtered. The filter cake obtained is separated from the flocculent precipitate with a high density precipitated at the bottom of the brine (i.e., the hydrolysis and condensation product of KH560) and the special flame retardant for polyurethane rigid foam by water flotation (also known as flotation method). The obtained special flame retardant for polyurethane rigid foam is dried at 100°C for 12 hours to finally obtain a special flame retardant powder for polyurethane rigid foam. The other contents are the same and will not be repeated.
[0099] After measurement and calculation, the polyurethane rigid foam special flame retardant powder obtained in Comparative Example 3 weighed 432.9g, with a yield of 82.9% and a density of 1.07g / cm 3 .
[0100] It can be seen that compared with Example 1, in Comparative Example 3, the amount of sodium hydroxide added was adjusted from 2g to 9g, and the yield of the target product obtained was reduced from 96.4% to 82.9%, a decrease of 13.5%; the density was reduced from 1.12g / cm 3 Reduced to 1.07g / cm 3Preliminary analysis revealed that during the experiment, it was observed on-site that with the continued addition of KH560, a large amount of flocculent precipitate, representing the hydrolysis and polycondensation product of KH560, appeared in the solution after 7 minutes (no sodium sulfamate was added at this time). After the reaction, the flocculent precipitate was very viscous, causing severe clogging of the filter paper during vacuum filtration. The filtration time lasted for as long as 12 hours, significantly impacting production capacity.
[0101] Comparative Example 4
[0102] Comparative Example 4 provides a method for preparing a flame retardant for polyurethane rigid foam. Compared with the preparation steps of Example 1, the difference is that the amount of sodium hydroxide added is 0.05 g, and the mass ratio of ethanol aqueous solution to sodium hydroxide is 998:0.05. The other contents are the same and will not be repeated.
[0103] After the reaction was completed, the polyurethane rigid foam flame retardant powder obtained in Comparative Example 4 weighed 430.1 g, with a yield of 82.4% and a density of 1.07 g / cm 3 .
[0104] It can be seen that compared with Example 1, the amount of sodium hydroxide in Comparative Example 4 was reduced from 2g to 0.05g, and the yield of the target product was reduced from 96.4% to 82.4%, a decrease of 14.0%; the density was reduced from 1.12g / cm 3 Reduced to 1.07g / cm 3 Preliminary analysis showed that when the amount of sodium hydroxide used was small, the pH value of the system tended to be neutral. Since KH560 hydrolyzed very slowly, only a small amount of KH560 reacted on the surface of the hollow silica microspheres. Consequently, there were few epoxy functional groups on the surface of the hollow silica microspheres that reacted with sodium aminosulfonate, resulting in a significant decrease in the yield of the target product.
[0105] Figure 2 The following are the Fourier transform infrared spectroscopy analysis results of hollow silica microspheres and the flame retardant for polyurethane rigid foam prepared in Example 1. Figure 2 As shown, hollow silica microspheres have a wavelength of 3300-3500 cm -1 The absorption peak corresponds to the stretching vibration absorption peak of hydroxyl, indicating that there are hydroxyl groups on the surface of silica microspheres that react with the hydrolyzed silanol groups of the silane coupling agent. -1 The absorption peak corresponds to the characteristic absorption peak of CH alkane, indicating that KH560 has been grafted onto its surface, because silica and sodium sulfamate do not have CH alkane functional groups. After sodium sulfamate grafting, the most obvious is the addition of 1160cm -1 , 1097cm -1 , 1035cm-1 , 816cm -1 and 690cm -1 These five absorption peaks correspond to the asymmetric stretching vibration absorption peak of the sulfonic acid on the benzene ring, the corresponding vibration absorption peak of CH on the benzene ring, the symmetric stretching vibration absorption peak of the sulfonic acid on the benzene ring, the vibration peak of the tertiary amine (i.e., the functional group produced by the reaction of the epoxy functional group and the amino functional group), and the stretching vibration absorption peak of SO on the sulfonic acid. The appearance of these five peaks fully demonstrates that sodium aminosulfonate is successfully fixed to the surface of the silica microspheres through chemical bonds. The test results show that the flame retardant for polyurethane rigid foam of the present invention has been successfully prepared.
[0106] The yield and density of the flame retardant powder for polyurethane rigid foam prepared in Examples 1 to 16 are summarized in Table 1 below:
[0107] Table 1 Yield and density of the flame retardant powder for polyurethane rigid foam obtained in Examples 1 to 16
[0108]
[0109]
[0110] As an important precursor for the preparation of polyurethane rigid foam, combined polyether is an important existing synthetic polymer material. It is a brown viscous liquid with a density of generally 1.10-1.15 g / cm 3 The specific value of the density depends on its components and processing technology. During the preparation of polyurethane rigid foam, a solid flame retardant is added to the combined polyether. When the density of the solid flame retardant is greater than that of the combined polyether, the solid flame retardant settles to the bottom of the combined polyether; when the density of the solid flame retardant is less than that of the combined polyether, the solid flame retardant floats on top of the combined polyether. Both situations will lead to uneven dispersion of the two, affecting the flame retardant effect of the polyurethane rigid foam. Only when the density of the solid flame retardant is the same as or not much different from that of the combined polyether, the solid flame retardant will be suspended in the combined polyether, achieving uniform distribution and ensuring the flame retardant effect of the polyurethane rigid foam.
[0111] The density of the flame retardant powder for polyurethane rigid foam prepared in Examples 1 to 16 ranges from 1.08 to 1.15 g / cm 3 In actual production, according to the actual situation of the combined polyether used, a polyurethane rigid foam special flame retardant powder with a density similar to that used can be prepared. For example, the density of the combined polyether used is 1.12cm 3 When the density is 1.12g / cm 3 Special flame retardant powder for polyurethane rigid foam; confirmed by production and experimental process, 1.11~1.13g / cm 3Special flame retardant powder for polyurethane rigid foam is also available.
[0112] From the above-mentioned Example 1, Example 15, and Example 16, when other conditions remain unchanged, by adjusting the density of the hollow silica microspheres, the density of the target product, the flame retardant powder for polyurethane rigid foam, is increased or decreased accordingly without affecting the result of the chemical reaction yield; in the actual production process, the number of experiments can be increased, and the pattern of increase or decrease of the density of the hollow silica microspheres can be found by changing the density of the hollow silica microspheres, so that the density of the target product, the flame retardant powder for polyurethane rigid foam, can be accurately adjusted according to the density of the combined polyether when preparing polyurethane rigid foam on site, so that the densities of the two are the same or not much different, thereby achieving the suspension and dispersion of the solid flame retardant of the present invention in the combined polyether in the liquid state, so that the two are evenly distributed.
[0113] In addition, since the chemical bonds of aminosulfonates are bound to the surface of silica microspheres, they will not be lost even if they absorb water; at the same time, the amino group can react with the epoxy functional group to generate hydroxyl and imino groups, which can react with the precursor isocyanate in the polyurethane rigid foam, thereby being firmly fixed inside the polymer to form a reactive flame retardant, ensuring the flame retardant properties of the polyurethane rigid foam.
[0114] It should be noted that, in the above embodiments of the present invention:
[0115] (1) The deionized water used may be replaced by pure water.
[0116] (2) The ethanol aqueous solution is prepared by mixing ethanol and deionized water in a mass ratio of preferably 980:18. Other ratios can also be used according to actual conditions.
[0117] (3) An alkaline environment can be achieved by adding sodium hydroxide, or other alkaline substances such as potassium hydroxide can be used instead.
[0118] (4) In addition to KH560, the silane coupling agent with epoxy functional groups can also be replaced by other silane coupling agents with epoxy functional groups such as 3-(2,3-epoxypropoxy)propyltriethoxysilane and 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane.
[0119] (5) The hollow silica microspheres used in the present invention are commercially available raw materials, and have a hollow structure with closed-cell characteristics, that is, the internal cavity of the hollow silica microspheres is relatively isolated from the external environment and is not connected to each other.
[0120] (6) The density is 1.06 g / cm 3The silica hollow microspheres of the desired particle size were placed in the brine using the water flotation method, the precipitated silica hollow microspheres were removed, and the completely floated silica hollow microspheres were removed, and the silica hollow microspheres in the suspended state in the brine were retained. The silica hollow microspheres were fully washed with water and dried to obtain a density of 1.06 g / cm 3 hollow silica microspheres.
[0121] (7) In order to ensure the production capacity and yield of the target product, in actual production, strict attention should be paid to controlling the reaction temperature. The reason is that when the temperature of the reaction system is too low, the hydrolysis rate of the silane coupling agent KH560 is too slow; when the temperature is too high, a large number of side reactions will occur, and the hydrolyzed silanol groups will undergo self-condensation reaction without reacting with the hydroxyl groups on the hollow silica microspheres.
[0122] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent replacements and improvements made within the spirit and principles of the present application should be included in the scope of protection of the present application.
Claims
1. A method for preparing a flame retardant specifically for polyurethane rigid foam, characterized in that: The steps are as follows: In an ethanol aqueous solution, under an alkaline environment, hollow silica microspheres react with a silane coupling agent with an epoxy functional group to obtain surface-activated hollow silica microspheres; the surface-activated hollow silica microspheres react with basic aminosulfonate or aminosulfonate guanidine. After the reaction is completed, post-treatment is performed to obtain a flame retardant specifically for polyurethane rigid foam.
2. The method for preparing a flame retardant specifically for polyurethane rigid foam according to claim 1, characterized in that: The ethanol aqueous solution is prepared by mixing ethanol and deionized water in a mass ratio of 980:
18.
3. The method for preparing a flame retardant specifically for polyurethane rigid foam according to claim 1, characterized in that: The alkaline environment is sodium hydroxide or potassium hydroxide.
4. The method for preparing a flame retardant specifically for polyurethane rigid foam according to claim 1, characterized in that: The alkaline environment is sodium hydroxide, and the mass ratio of the ethanol aqueous solution to the sodium hydroxide is 998:0.2-2.
5. The method for preparing a flame retardant specifically for polyurethane rigid foam according to claim 1, characterized in that: The mass ratio of the hollow silica microspheres, the silane coupling agent, and the basic aminosulfonate or guanidine aminosulfonate is 300-500:16.5-27.5:75-125.
6. The method for preparing a flame retardant specifically for polyurethane rigid foam according to claim 1, characterized in that: The density of the hollow silica microspheres is 1.03 to 1.09 g / cm 3 The particle size of the hollow silica microspheres is 7 to 48 μm.
7. The method for preparing a flame retardant specifically for polyurethane rigid foam according to claim 1, characterized in that: The basic aminosulfonate is selected from sodium sulfamate or potassium sulfamate.
8. The method for preparing a flame retardant specifically for polyurethane rigid foam according to claim 1, characterized in that: The silane coupling agent with epoxy functional group is KH560.
9. The method for preparing a flame retardant specifically for polyurethane rigid foam according to claim 1, characterized in that: The reaction temperature of the hollow silica microspheres and the silane coupling agent is 40-90°C.
10. The method for preparing a flame retardant specifically for polyurethane rigid foam according to claim 1, characterized in that: The post-processing method includes: vacuum filtration and drying the obtained filter cake.